Nilai-nilai Religius dalam Novel #BERHENTIDIKAMU Karya dr. Gia Pratama Sebagai Bahan Pembelajaran Apresiasi Sastra - Sauri, Sopyan (Universitas Mathla'ul Anwar Banten, 2021)
The purpose of this research is to describe the religious values contained in the novel #berhentidikamu by dr. Gia Pratama. The research method used in studying the novel #berhentidikamu by dr. Gia Pratama is a descriptive qualitative method. The object of this research is the religious values in the novel #berhentidikamu by dr. Gia Pratama published by PT Mizan Pustaka in 2018. The data collection techniques used in this study used two techniques. The first technique is literature study technique. Literature study technique is a technique used to find written sources related to research. The second technique used is the analysis technique. The analysis technique is used to analyze the data in the written form contained in the novel #berhentidikamu by Dr. Gia Pratama.Results of data analysis on the novel #berhentidikamu by dr. Gia Pratama can be concluded that the religious values contained in the novel are divided into three major groups of religious values, namely (1) Attitude and Behavior (Akhlak) in which there is a religious value of faith in Allah SWT and Taqwa. (2) Norms of Life (Fiqh) in which there is a religious value of circumcision. (3) Attitude (Akhlak) in which there are religious values of Patience, Humility, Tawakal, Sincerity, and Discipline.The results of the analysis of religious values in the novel #berhentidikamu by dr. Gia Pratama can be used as a learning material for literary appreciation. It is used as a learning material for literary appreciation because the novel contains religious values that can be imitated and applied in everyday life